The PPAR Ω Pocket: Renewed Opportunities for Drug Development - Åsmund Kaupang; Trond Vidar Hansen (PPAR Research)
The past decade of PPARγ research has dramatically improved our understanding of the structural and mechanistic bases for the diverging physiological effects of different classes of PPARγ ligands. The discoveries that lie at the heart of these developments have enabled the design of a new class of PPARγ ligands, capable of isolating central therapeutic effects of PPARγ modulation, while displaying markedly lower toxicities than previous generations of PPARγ ligands. This review examines the emerging framework around the design of these ligands and seeks to unite its principles with the development of new classes of ligands for PPARα and PPARβ/δ. The focus is on the relationships between the binding modes of ligands, their influence on PPAR posttranslational modifications, and gene expression patterns. Specifically, we encourage the design and study of ligands that primarily bind to the Ω pockets of PPARα and PPARβ/δ. In support of this development, we highlight already reported ligands that if studied in the context of this new framework may further our understanding of the gene programs regulated by PPARα and PPARβ/δ. Moreover, recently developed pharmacological tools that can be utilized in the search for ligands with new binding modes are also presented.